Gods, Buddhas, and Organs Buddhist Physicians and Theories of Longevity in Early Medieval Japan - Drott, Edward R. (2010)
This article examines medical works aimed at nourishing life and promoting longevity composed or compiled by Buddhist priests in early medieval Japan, focusing on the Chōseiryōyōhō and the Kissayōjōki. These texts provide an especially useful aperture through which to explore the relationship of medical and religious knowledge in medieval Japan, since theories about the aging process were based on fundamental beliefs about both the structure of bodies and the nature of the forces thought to animate them. A comparison of the different types of practices these texts recommended to forestall physical degeneration and spiritual dissipation provides concrete examples of the ways in which Buddhist physicians, or "priest-doctors" (sōi), combined Chinese medical theories with knowledge gleaned from Buddhist scriptures, and sheds light on the various conceptualizations of the body that emerged in the intersection of these traditions.
Keywords: Buddhism; Flavors; Human organs; Liver; Longevity; Medical Practice; Physicians; Priests; Religious Studies; Syllables